Estimation of Thiamine, Riboflavin and Pyridoxine from LPC of Some Plants - Sayyed Iliyas2, K.V. Badar1* and (Journal of Experimental Sciences, 2010)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; background: white; padding-bottom: 0in; border-left: medium none; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> Thiamine, riboflavin and pyridoxine were estimated from leaf protein concentrate (LCP) of twenty plants viz Adhatoda vasica, Benincasa hispida, Brassica oleracea V. botrytis, Brassica oleracea V. Capitata, Cassia tora, Centella Asiatica, Coccinia grandis, Coriandrum sativum, Cucusmis sativus, Eclipta alba, Erythrina varegata, Medicago sativa, Moringa oleofera, Phaseolus valgaris, Raphanus sativus, Sesbania grandiflora, Solanum nigrum, Trigonella foenum graecum and Vigna mungo. Higher yield of thiamine was recorded in LPC of Brassica oleracea V. botrytis, Brassica oleoracea V. capitata, Coriandrum sativum, Raphanus sativus and Vigna mungo. LPC of Adhatoda vasica and Trigonella foenum graecum yielded maximum riboflavin while more pyridoxine was estimated from Brassica oleracea, V. botrytis and Bennicasa hispida. <div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; padding-bottom: 0in; border-left: medium none; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> 1Department of Botany, Yeshwantrao Chavan College, Sillod, Dist- Aurangabad (M.S.), India; 2Department of Botany, AKI’S Poona College of arts, Science and commerce, Pune camp, Pune (M.S.), India * Corresponding Author, Email: badarkakasaheb@yahoo.in Please Cite This Article As: K.V. Badar and Sayyed Iliyas. 2010. Estimation of Thiamine, Riboflavin and Pyridoxine from LPC of Some Plants. J. Exp. Sci. 1(2): 12-14.